2021
DOI: 10.1186/s12872-021-02423-6
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-to-hemoglobin ratio as a valuable predictor of long-term all-cause mortality in coronary artery disease patients with congestive heart failure

Abstract: Background The platelet-to-hemoglobin ratio (PHR) has emerged as a prognostic biomarker in coronary artery disease (CAD) patients after PCI but not clear in CAD complicated with congestive heart failure (CHF). Hence, we aimed to assess the association between PHR and long-term all-cause mortality among CAD patients with CHF. Methods Based on the registry at Guangdong Provincial People’s Hospital in China, we analyzed data of 2599 hospitalized patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…This is because the release of various mediators during the inflammatory response, as well as increased platelet counts in the circulation, cause thrombosis-related complications in patients with congestive heart failure (CHF). 16 Therefore, this study was aimed at determining the magnitude of different leukocyte and platelet count abnormalities and their associated factors among patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the release of various mediators during the inflammatory response, as well as increased platelet counts in the circulation, cause thrombosis-related complications in patients with congestive heart failure (CHF). 16 Therefore, this study was aimed at determining the magnitude of different leukocyte and platelet count abnormalities and their associated factors among patients with heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…In ROC analysis, a PLR threshold of 132.6 was shown to have 68.5% specificity and 71.3% sensitivity for the prediction of clinical outcomes (AUC = 0.704, p < 0.001) [ 37 ]. A Chinese retrospective observational cohort on 2599 patients with CAD complicated by congestive heart failure, reported that high platelet to hemoglobin ratio (PHR) was associated with a higher risk of all-cause mortality in unadjusted, age- and gender-adjusted, and fully adjusted models over a median follow-up of 5.2 years [ 38 ]. Patients in the upper quartile of PHR were shown to have an increased risk of all-cause mortality compared to those in the lowest quartile [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…PHR higher than 1.92 is associated with all-cause mortality, cardiac mortality, re-admission, and MACE and/or cerebrovascular events in these patients [ 12 ]. Bao et al showed that a PHR higher than 1.69 was correlated with an increased risk of long-term all-cause mortality in patients with CAD and CHF [ 11 ]. In our study, we found that in-hospital mortality increased more than 2.5 times in patients with a PHR above 1.99.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline data for all patients included demographic characteristics, medical history, laboratory tests, electrocardiographic, and echocardiographic results. PHR was obtained by the ratio of platelet measured in 10 9 /L and hemoglobin measured in gram/L in the hemogram of admission [ 11 ]. The patients were receiving medical treatment according to current European Society of Cardiology guidelines [ 4 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation